Tipificación de los sistemas de producción agricolas en la zona norte del embalse Daule Peripa. - Vera Vásquez, Fabián Fabricio (2014)
This work presents the characterization of agro- production systems in the catchment area of the dam Duale Peripa , for which a representative survey was conducted and randomized 100 farmers covering 10 localities , it considered various issues affecting productivity and the lives of farmers , among them : social aspects of producers, technicians crops , and marketing of products , also the main problems affecting the area of influence of this study were determined. The results show that the dominant systems of production are represented by crops : cocoa , banana , passion fruit , palm , corn, citrus , papaya , coffee, pasture, also , that 87.5 percent of the population is economically suitable age , the producers surveyed 93.75 represents the male gender, 28.13 percent ventures into social programs equally, 62.5 percent of producers makes mechanization and the same number applies any pesticide, 43.75 percent of respondents performed fertilization , in regard to the present problems , only 18.75 percent use more than twenty percent of its land area , 46.8 percent agreed that funding was the problem main , followed by 43.75 percent who stated that was the state of inoperability of the irrigation systems. Regarding associations or cooperatives the presence of two but with a high degree of disorganization was evident , as a consequence , the production levels are directly affected by the null technical advice and the level of investment , alongside deteriorating infrastructure negatively impacts the ability of the area is underutilized , the technology used depends on the economic capacity of the producer, few farmers have agriculture as a single work and mostly it is taken as secondary .